2017
DOI: 10.1121/1.4979593
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tone-vocoding on spatial release from masking for old, hearing-impaired listeners

Abstract: Old, hearing-impaired listeners generally benefit little from lateral separation of multiple talkers when listening to one of them. This study aimed to determine how spatial release from masking (SRM) in such listeners is affected when the interaural time differences (ITDs) in the temporal fine structure (TFS) are manipulated by tone-vocoding (TVC) at the ears by a master hearing aid system. Word recall was compared, with and without TVC, when target and masker sentences from a closed set were played simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
(121 reference statements)
1
6
0
Order By: Relevance
“…Figure 8B shows the deviation from the predictions for the listeners with impaired hearing. In addition, as has been found by others (Jerger et al, 1984;Neher et al, 2011Neher et al, , 2017Bernstein and Trahiotis, 2016, 2018King et al, 2017), low-frequency PTA was a significant predictor both of ITD sensitivity and of BRM.…”
Section: Peripheral Loss and Srmsupporting
confidence: 81%
“…Figure 8B shows the deviation from the predictions for the listeners with impaired hearing. In addition, as has been found by others (Jerger et al, 1984;Neher et al, 2011Neher et al, , 2017Bernstein and Trahiotis, 2016, 2018King et al, 2017), low-frequency PTA was a significant predictor both of ITD sensitivity and of BRM.…”
Section: Peripheral Loss and Srmsupporting
confidence: 81%
“…No significant correlations were found between binaural TFS sensitivity and speech recognition in that study (King et al 2017). However, Neher et al (2012) observed a significant association between binaural TFS sensitivity and performance in a test of spatial speech recognition using the same sentence corpus as both King et al (2017) and Strelcyk and Dau (2009). Both King et al (2017) and Neher et al (2012) used a masker of two female talkers.…”
Section: Tfs and Speech Recognitionmentioning
confidence: 62%
“…However, Neher et al (2012) observed a significant association between binaural TFS sensitivity and performance in a test of spatial speech recognition using the same sentence corpus as both King et al (2017) and Strelcyk and Dau (2009). Both King et al (2017) and Neher et al (2012) used a masker of two female talkers. In contrast, L} ocsei et al (2016) found no evidence of a relation between binaural TFS and matrix sentence recognition in different types of noise, both co-located and separated from the target.…”
Section: Tfs and Speech Recognitionmentioning
confidence: 95%
See 2 more Smart Citations